SPECIAL CONSIDERATIONS REGARDING WARFARIN DOSE TITRATION IN PATIENTS WITH ATRIAL FIBRILLATION DEPENDING ON CLINICAL FACTORS - E. L. Artanova; E. V. Saleeva; I. M. Sokolov; Y. G. Shvarts (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To study the relations of clinical characteristics and individual warfarin dose titration in patients with atrial fibrillation. Material and methods. Period of warfarin dose titration was analyzed in 68 patients with atrial fibrillation due to ischemic heart disease. Adjusted warfarin dose in milligram, duration of dose titration in days and maximal international normalized ratio (INR) were taken into account. Sex, age, history of myocardial infarction and stroke, concomitant diseases, amiodarone therapy were considered among clinical characteristics. Results. Adjusted warfarin dose was significantly higher in obesity , and it was lower in case of experienced myocardial infarction. The INR highest levels and maximal amplitudes of its fluctuations were observed in patients with thyroid gland nodes and smokers. Period of warfarin dose titration was longer in patients treated with amiodarone. Conclusion. Warfarin dose titration in patients with atrial fibrillation depends on the presence of myocardial infarction, obesity , thyroid nodular changes, smoking and amiodarone treatment.